ANALISIS PRAKTEK WAQF AL NUQUD (WAKAF UANG) PERSPEKTIF HUKUM ISLAM (Kajian Mazhab Syafi’i dan Hanafi) - Khusnul Khotimah; Masrokhin (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
Cash waqf is a form of waqf that has an important role in supporting social and economic development in Muslim societies. The Syafi’i school considers cash waqf as waqf that must be earmarked for charity directly. According to the Syafi’i school, waqf money cannot be withdrawn by the waqif or passed on to his heirs. The money must be managed and used in accordance with the stated purpose of the waqf. Waqf recipients are responsible for ensuring good management and utilizing the money for the benefit of the ummah. On the other hand, the Hanafi School has a more flexible approach to cash waqf. According to the Hanafi School, cash waqf can be withdrawn by the waqif as long as he is still alive, unless otherwise agreed in the waqf contract